DARI RITUAL KE KOREOGRAFI PARTISIPATORIS: NILAI PENDIDIKAN DALAM KARYA BAKAR BATU INDONESIA ART MOVEMENT - Muhammad Ilham Mustain Murda; Suwarjiya; Rahmani; Dewi Rukmini Sulistyawati (Greget: Jurnal Kreativitas dan Studi Tari, 2026)
Bakar Batu is widely known as a communal cooking ritual in the Papuan Highlands. In the work created by Indonesia Art Movement, this ritual was reworked into a participatory performance involving bodies, sound, material objects, food, narration, and audience engagement. This article examines how Bakar Batu was transformed from ritual practice into participatory choreography and what educational values emerged from that process. The study focuses on the performance held on March 23, 2024, at KedIAMan Indonesia Art Movement, Jayapura, involving 32 performers and approximately 150 spectators. This research uses a qualitative approach through practice-based research and choreographic autoethnography. Data were collected from the creative proposal, audiovisual documentation, the artist’s reflective notes, and semi-structured interviews with performers, a Hubula youth figure, and spectators. The findings show that the work generated five layers of educational value: bodily education, ecological-material education, social-hospitality education, musical-aesthetic education, and cultural-intergenerational education. The performance demonstrates that learning about tradition can occur not only through verbal explanation, but also through participation, sensory experience, communal eating, and direct encounter with local knowledge. This article argues that participatory choreography can function as a living space for cultural education rooted in Papuan embodied knowledge.